Description of New Neotropical Berosini Larvae: Derallus paranensis and Hemiosus dejeanii (Coleoptera: Hydrophilidae) - Archangelsky, Miguel (2005)
The larval stages of the Neotropical species Derallus paranensis Oliva, 1981 and Hemiosus dejeanii (Solier, 1849) are described and figured for the first time. Notes on the bionomics of these two species are included. Larvae of D. paranensis and H. dejeanii are compared to those of other Derallus Sharp and Hemiosus Sharp species. Comparative notes to differentiate larvae of two genera related to Derallus, Allocotocerus Kraatz and Regimbartia Zaitzev are provided.